2009
DOI: 10.1007/978-1-60327-565-1_11
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Host and Phage mRNA Expression During Infection Using Real-Time PCR

Abstract: Real-time, or quantitative PCR is a valuable technique useful in bacteriophage research to quantify the abundance of phage or host gene transcripts. It can be used during the infection cycle both to monitor the expression of individual viral transcripts and to compare relative gene expression levels throughout the infection cycle. It is fairly economical to conduct and is useful in bacteria-phage systems where obtaining high yields of RNA is problematic. To perform real-time PCR it is simply necessary to know … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The primer details are presented in Supplementary Table 1 . All data were analyzed statistically using the two-tailed Student’s t -test ( Clokie, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primer details are presented in Supplementary Table 1 . All data were analyzed statistically using the two-tailed Student’s t -test ( Clokie, 2009 ).…”
Section: Methodsmentioning
confidence: 99%
“…This method can also be applied in other experiments that require detection of a “neutralized” phage, which is merely a phage that is not active against bacteria. Notably, qPCR has already been applied for phage detection in other (than phage neutralizing) conditions: in phage cultures ( Edelman and Barletta, 2003 ; Clokie, 2009 ; Anderson et al, 2011 ; Refardt, 2012 ; Dieterle et al, 2016 ), food ( Imamovic and Muniesa, 2011 ; Flannery et al, 2014 ; Perrin et al, 2015 ; Parente et al, 2016 ; Hartard et al, 2017 ; Muhammed et al, 2017 ), environmental samples ( Farkas et al, 2015 ; Kunze et al, 2015 ; Unnithan et al, 2015 ; Mankiewicz-Boczek et al, 2016 ), and in feces ( Imamovic et al, 2010 ; Chehoud et al, 2016 ), where some interference from antibodies cannot be excluded ( Majewska et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitative polymerase chain reaction (qPCR) detection of eukaryotic viruses in environmental and human or animal samples is a standard and commercialized method ( Watzinger et al, 2004 ; Hmaied et al, 2015 ). Bacteriophages have been quantitatively analyzed and discriminated by real-time qPCR directly in microbiological cultures, and the authors found this method to be a good alternative to the plaque assay ( Edelman and Barletta, 2003 ; Clokie, 2009 ; Anderson et al, 2011 ; Refardt, 2012 ; Dieterle et al, 2016 ). Real-time PCR has been further demonstrated as applicable for a rapid screening allowing phage detection in food (milk, fruits, vegetables, seafood, meat) ( Imamovic and Muniesa, 2011 ; Flannery et al, 2014 ; Perrin et al, 2015 ; Parente et al, 2016 ; Hartard et al, 2017 ) and water samples ( Farkas et al, 2015 ; Kunze et al, 2015 ; Unnithan et al, 2015 ; Mankiewicz-Boczek et al, 2016 ) or in feces ( Imamovic et al, 2010 ; Chehoud et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%